Gambaran Pentingnya Sarana Dan Prasarana Dalam Pelaksanaan Layanan Konseling Individual Di Sekolah - Tumanggor, Athalia; Ahmad, Riska; Syukur, Yarmis (Prodi Bimbingan dan Konseling Islam, 2023)
Guidance and counseling is an integral part of the education system carried out by a guidance counselor/counselor. This is in line with efforts to become independent and provide facilities to students to help achieve optimal development. In guidance counseling one service that is quite important, namely individual counseling services. Individual counseling is the process of providing assistance carried out by the counselor with someone personally or directly. This means that it requires a special room so that confidentiality is maintained and the client feels safe to express the problems he is experiencing. However, there are still many schools that have not provided a special room for the implementation of individual counseling services, the impact is that other students or teachers will be able to see and listen to the individual counseling process that is being carried out. The research used in this article is qualitative with a case study approach. The data in this article were collected through questionnaires and interview guides. The research informants were 10 counseling teachers/counselors. From the results of the study it was found that facilities and infrastructure were needed, especially the availability of individual counseling rooms in order to create a conducive and good relationship or atmosphere between the counselor and the client and to make the counseling process more optimal.